A Metal–Organic Framework with a Pore Size/Shape Suitable for Strong Binding and Close Packing of Methane. (4th March 2016) - Lin, Jiao‐Min; He, Chun‐Ting; Liu, Yan; Liao, Pei‐Qin; Zhou, Dong‐Dong; Zhang, Jie‐Peng; Chen, Xiao‐Ming
Abstract: Much effort has been devoted to develop new porous structures for methane storage. We report a new porous coordination framework showing exceptional methane uptakes (e.g. 263 v / v at 298 K and 65 bar) and adsorption enthalpies (21.6 kJ mol −1 ) as high as current record holders functionalized by open metal sites. Computational simulations demonstrated that the hierarchical pore structure consisting of single‐wall nanocages has suitable sizes/shapes and organic binding sites to enforce not only strong host–methane and methane–methane interactions but also dense packing of methane molecules. Abstract : Eine hochdichte Methanspeicherung wird von einem Metall‐organischen Gerüst mit hierarchischem Porensystem bestehend aus einwandigen Nanokäfigen und starken organischen Bindungsstellen erzielt. Diese erzwingen nicht nur starke Wirt‐Methan‐ und Methan‐Methan‐Wechselwirkungen, sondern auch eine dichte Packung der Methanmoleküle.